Competências comportamentais na revolução digital: uma perspectiva do feminino no novo mercado de trabalho - Basilio, Patrícia Cristina de Souza (2022)
The research assesses how behavioral skills, also called soft skills, favor employability in the labor market amidst the new technological revolution, and analyzes whether these differentials contribute to the rise of women, in relation to men in companies. In a society marked by patriarchal power, women fight for a balance in numbers while celebrate small advances in diversity. Related to bussiness, gender equality has been seen as strategy for economic growth, spread of good moral values and social demand since the 1930’s. In this project, we intend to show the extent to which demands for qualification presented by companies and highlighted by human resources consultancies generate general benefits for professionals, especially women